2021
DOI: 10.3390/jcm10132902
|View full text |Cite
|
Sign up to set email alerts
|

ISIDOG Consensus Guidelines on COVID-19 Vaccination for Women before, during and after Pregnancy

Abstract: Introduction. Sars-CoV-2 infection poses particular problems in pregnancy, as the infection more frequently causes severe complications than in unaffected pregnant women or nonpregnant women with SARS-CoV-2 infection. Now that vaccination is available and rapidly being implemented worldwide, the question arises whether pregnant women should be vaccinated, and if so, whether they should receive priority. Methods. Available scientific data and available guidelines about vaccination against SARS-CoV-2 were collec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…Although pregnant women were not involved in the COVID-19 vaccine development trials, they have had access to these vaccinations since the FDA approved Pfizer/BioNTech immunization for pregnant women in early 2021, followed by the same reaction from the European Medicines Agency [5,6]. Because none of the COVID-19 vaccines contain live viruses or adjuvants that could harm an unborn child, both the American College of Obstetricians and Gynecologists [7] and the Society for Maternal-Fetal Medicine have consistently advocated for the availability of the COVID-19 vaccine to pregnant and lactating women, and both professional societies, as well as the CDC, now recommend vaccination in these populations [8]. In Romania, the decision to promote COVID-19 vaccination during pregnancy was reached later in September 2021, after more data about safety became available.…”
Section: Introductionmentioning
confidence: 99%
“…Although pregnant women were not involved in the COVID-19 vaccine development trials, they have had access to these vaccinations since the FDA approved Pfizer/BioNTech immunization for pregnant women in early 2021, followed by the same reaction from the European Medicines Agency [5,6]. Because none of the COVID-19 vaccines contain live viruses or adjuvants that could harm an unborn child, both the American College of Obstetricians and Gynecologists [7] and the Society for Maternal-Fetal Medicine have consistently advocated for the availability of the COVID-19 vaccine to pregnant and lactating women, and both professional societies, as well as the CDC, now recommend vaccination in these populations [8]. In Romania, the decision to promote COVID-19 vaccination during pregnancy was reached later in September 2021, after more data about safety became available.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that antibodies produced by mothers infected with COVID-19 pass through the placenta to the fetus [8,9]. Although the risk and symptoms of pregnant women infected with COVID-19 are the same as those of non-pregnant people [10,11], several studies have found that, compared with age-matched non-pregnant women, pregnant women are more likely to have severe symptoms after being infected with COVID-19, especially when combined with risk factors such as advanced age, preeclampsia, obesity, diabetes, and high blood pressure [11][12][13]. The risk of neonatal complications such as premature delivery, meconium staining, respiratory distress, and perinatal death increases as well [12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of publications demonstrate the safety of COIVD-19 vaccination during pregnancy [7][8][9], but it remains important for researchers to evaluate the safety and tolerability of COVID-19 vaccination during pregnancy in local populations of women. The American College of Obstetricians and Gynecologists, the US Centers for Disease Control and Prevention, the UK Royal College of Obstetricians and Gynaecologists, and the Polish Society of Obstetrics and Gynecology recommend vaccination of pregnant women against COVID-19 [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%